1974
DOI: 10.1073/pnas.71.7.2823
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Ribosomal DNA from Xenopus laevis Has Heterogeneous Spacer Lengths

Abstract: Eco R, restriction endonuclease makes two cuts in each repeating unit of amplified ribosomal DNA (rDNA) from Xenopus laevis. The locations of these cuts have been established by comparison of the secondary structure of single-stranded Eco RI fragments (as visualized in the electron microscope) with that of X. laevis rRNAs and of long strands of uncut rDNA. Of the two classes of fragments generated, the smaller one contains 90% of the 28S rRNA gene, has a duplex molecular weight of 3.0 X 106 and is homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…A review of some of the frequently cited papers that propose homogeneous rRNA operons revealed that their conclusions were largely based either on techniques which would not reveal relatively low levels of sequence variations (2,16,18,27,34,35) or on analyses of a fraction of a gene or a few genes of an organism (18,27). For example, endonuclease restriction analysis of genomic DNA or cloned rDNA would fail to detect nucleotide substitutions that did not destroy or create restriction sites for the enzymes in use (2,18,34); electron microscopic observation of heteroduplex DNA formation is limited to detection of large unpaired regions or loops (34); oligonucleotide cataloguing would reveal only a maximum of 45% of the information of a 16S rRNA (28); and the reverse transcription-based sequencing of rRNAs suffers from quite extensive ambiguities in sequence results (16,28), which could be, at least in some cases, due to the presence of different rRNA species. Taken together, the presence of distinct types of an rRNA species in a single organism could be a common rather than unusual phenomenon in nature.…”
Section: Discussionmentioning
confidence: 99%
“…A review of some of the frequently cited papers that propose homogeneous rRNA operons revealed that their conclusions were largely based either on techniques which would not reveal relatively low levels of sequence variations (2,16,18,27,34,35) or on analyses of a fraction of a gene or a few genes of an organism (18,27). For example, endonuclease restriction analysis of genomic DNA or cloned rDNA would fail to detect nucleotide substitutions that did not destroy or create restriction sites for the enzymes in use (2,18,34); electron microscopic observation of heteroduplex DNA formation is limited to detection of large unpaired regions or loops (34); oligonucleotide cataloguing would reveal only a maximum of 45% of the information of a 16S rRNA (28); and the reverse transcription-based sequencing of rRNAs suffers from quite extensive ambiguities in sequence results (16,28), which could be, at least in some cases, due to the presence of different rRNA species. Taken together, the presence of distinct types of an rRNA species in a single organism could be a common rather than unusual phenomenon in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Each repeating unit contains one sequence coding for the precursor molecule to the rRNAs (pre-rRNA), and an adjacent more or less extended sequence, which is not complementary to pre-rRNA (for references see Birnstiel etal., 1971; Weil au er and Dawid, 1974;Schi bier et al , 1975 ;Spring et al , 1976). Miller and Beatty (1969) and Miller and Bakken (1972) have shown that this subdivision of the repeating unit can be directly visualized in the electron microscope after dispersion and spreading of the transcriptionally active nucleolar chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zakian (33) described a recombinant plasmid carrying the origin of the X. laevis mitochondrial DNA which can replicate in yeast cells. Our cleavage map of the 3.2-kb BamHI DNA segment in pXY65 shows a pattern different from that ofthe mitochondrial DNA (34) or ribosomal DNA (35,36) and, therefore, the segment probably is not derived from the mitochondrial DNA or ribosomal DNA of X. laevis. Moreover, the result of the DNA-DNA hybridization suggests that pXY65 contains a repetitive sequence(s) from the X. laevis chromosomes.…”
Section: Discussionmentioning
confidence: 64%